The origin and evolution of sewing technologies in Eurasia and North America. Issue 125 (December 2018) - d'Errico, Francesco; Doyon, Luc; Zhang, Shuangquan; Baumann, Malvina; Lázničková-Galetová, Martina; Gao, Xing; Chen, Fuyou; Zhang, Yue
Abstract: When, how, and following which paths hominins created the innovations that allowed them to colonize regions of the planet that were not suited to their thermal physiology is still a matter of inquiry. In this paper, we elaborate a theoretical framework to investigate the origin and diversification of bone needles, summarize the evidence for their emergence, create a large database of their morphometric and stylistic characters, and present results of the study of an exceptionally well-preserved collection of needles from Shuidonggou Locality 12 (SDG12), a site located in the Ningxia Hui Autonomous Region, Northern China, dated to ca. 11.2 ka BP. Bone needles are reported from 271 sites and 355 archaeological layers. Revision of the evidence shows they represent an original cultural innovation that emerged in Eurasia between 45–40 ka BP. Size differences between the earliest known specimens, found in Siberia and China, indicate needles may have been invented independently in these two regions. Needles from Eastern Europe may represent either an independent invention or a geographic extension of earlier Siberian and Caucasian sewing traditions. In Western Europe, needles appear during the Solutrean. The wider size range characteristic of Magdalenian specimens supports the idea that needles of different sizes were used in a variety of tasks. In China, the robust sub-circular needles found at sites dated between 35–25 ka BP are followed, between 26–23 ka BP, by small flat needles, which may represent an innovation associated with the microblades/microcores toolkit. At SDG12, technological, functional, and morphometric analyses of finished needles and manufacturing by-products identify two previously undetected reduction sequences for the production of needles of different size and, probably, function. The bone needles found at Paleoindian sites are the smallest and reflect a never previously achieved mastery in the production of such tools.